A Study on Quality and Reliability of websites using Functional testing and Usability testing - Jaganeshwari, K; Djodilatchoumy, S (International Journal of Computer Sciences and Engineering, 2018)
Usability Testing is the extent to which a product can be used by a particular user to achieve a defined target with effectiveness, efficiency and achieve satisfaction of use in a particular context. Usability is one of the important criteria to measure website quality and reliability. In addition to visual esthetics, usability of a website is a strong determinant for user’s satisfaction and pleasure. Designing user’s expectations is quite challenging job for any websites designer. Users have different usability requirements based on their age group and experience level. Therefore, it is very challenging to gather and implement the diverse nature of expectations against different users. Usability Testing is the extent to which a product can be used by a particular user to achieve a defined target with effectiveness, efficiency and achieve satisfaction of use in a particular context. There are five common usability testing characteristics that may lead to the best practices in the usability testing. The five characteristics are specific goals for each test, participants representing real users, participants doing real tasks, usability researcher observes and records what participants do and say and usability researcher doing the data analysis, diagnoses the problems, and recommends changes. Websites are the key aspect for satisfying the user’s demands. This papers aims to test the usability and reliability of websites.